Perkembangan Transaksi Mudharabah di Perbankan Syariah - Cipta, Hendra (ASY SYAR'IYYAH: JURNAL ILMU SYARI'AH DAN PERBANKAN ISLAM, 2017)
Mudaraba is a joint venture agreement between two parties, where the first party provides the entire capital is called shahibul mall and the second as the manager of the capital called mudharib. In other words, mudaraba is a term for the act of a person who entrusts his property to others to merchantability and split the profits for the two based on their agreement while losses to be borne by the property owner. Mudaraba concept was applied by sharia banks on savings accounts products, general investment accounts through deposits, special investment accounts, financing with the principle of profit sharing and mudaraba sukuk.Mudaraba as a principle of profit sharing is still practiced by Islamic banks in Indonesia with revenue sharing not lead to a profit and loss sharing. Here we can see that Islamic banks are still not ready to share profits and losses with the customer, but every effort will face profit and loss. However, we hope that in the future Islamic banks could apply the concepts of profit and loss sharing.